Reducing drug errors by engaging student nurses in medication management simulation. (2nd July 2019) - Edwards, Sharon L; Williams, Joyce; Lee, Mandy
Abstract : The occurrence of drug errors in the NHS has been much discussed in the media. Nurses are in a position to prevent drug errors, as they are often involved in administering medication or advising patients. To enable nurses to do this they need to be able to begin safe medication practice early in their education. This can be achieved through performing safe medication management simulations in undergraduate nursing courses. By setting up a number of patient scenarios in a skills laboratory, student nurses can practise medication management skills that are realistic in an environment where it is safe to make mistakes in order to ensure patient safety at all times.